Guyub Rukun Dance to Form Learning Motivation and Collaboration Ability Learners - Nurma Susanti (Javanologi: International Journal of Javanese Studies, 2024)
This study examines the integration of guyub rukun dance in elementary school learning as an effort to preserve local culture and strengthen character education. guyub rukun dance was chosen because it contains noble values such as togetherness, mutual cooperation, and social harmony that are relevant to the character formation of elementary school students. In addition, the simple dance movements and dynamic music are in accordance with the characteristics of elementary school-age students. This study uses a qualitative approach with a descriptive research type. The research data is in the form of information about the form of presentation, values, and the process of integrating guyub rukun dance in learning. Data sources include teachers, students, dance artists, and related documents. Data collection was carried out through participatory observation of the learning process, in-depth interviews with informants, photo and video documentation, and literature studies related to guyub rukun dance. Data validity was obtained through triangulation of sources, methods, and theories. The data analysis technique used the Miles and Huberman interactive model which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the integration of guyub rukun dance is effective in: (1) increasing students' understanding of local culture, (2) developing motor skills and creativity, (3) fostering character values such as cooperation, tolerance, and responsibility, and (4) creating a fun and meaningful learning atmosphere. This study recommends the importance of integrating traditional arts in learning to preserve local culture while forming positive character in students.